New Trends in Emerging Novel Nanosponges Drug Delivery: Investigation of Anti Inflammatory activity of Triphala hydrogel - Shinde, Snehal M.; More, Priti U.; Borkar, Smita P.; Yadav, Vishal D.; Zambare, Swapnil D.; Sontakke , Shrikrushn B. (Asian Journal of Pharmaceutical Research and Development, 2024)
Medical professionals have long had trouble delivering medications to the correct location in the body and controlling their release to prevent overdose. Nano-sponges are novel and complicated molecules, which have the ability to alleviate these challenges. Utilizing nano-sponges allows for precise drug delivery to the desired location. Nano-sponge technology gets better patient compliance by delivering drugs to strategic locations while also extending dosing intervals. Various drug delivery techniques, such as parenteral, transdermal, oral, and immunosuppressive drugs, involve Nano-sponges. In today's world, nanosponges are used in gastro-retentive drug delivery systems.